Коловратки рода Lecane (Rotatoria, Lecanidae) в фауне УССР - Овандер, Э.Н. (Вестник зоологии, 1980)
Six species and subspecies of the Lecane genus: L. (s. str.) elsa, L. (s. str.) brachydactyla, L. (s. str.) luna balatonica, L. (s. str.) arcuata, L. (M) elachis, L. (M) cf. mologensis are found for the first time in the Ukrainian SSR fauna. The last species was known in the USSR only in the Kalinin Region and L. (s. str.) luna balatonica is first mentioned for the USSR fauna.